Examine the Role of Women in IKS and the Gendered Dimensions of Traditional Knowledge - Mrs. Dedun Nirmabahen Vaksibhai; Dr. Ruchi Thakar (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Indigenous Knowledge Systems (IKS) encapsulate the unique cultural, ecological, and historical wisdom of indigenous communities globally. Within these frameworks, women often emerge as the primary custodians, responsible for the preservation, dissemination, and innovation of traditional knowledge. This paper explores the gendered dimensions inherent in IKS, emphasizing the contributions of women and the multifaceted challenges they encounter. The aim is to underscore the crucial importance of recognizing and supporting women’s roles in IKS, not only for the survival of indigenous cultures but also for sustainable development and environmental conservation. The paper concludes with actionable recommendations for integrating gender perspectives into IKS research and policy-making.